Choroidal Detachment after XEN Gel Stent Implantation. (8th March 2021) - Cutolo, Carlo Alberto; Negri, Letizia; Olivari, Sara; Cappelli, Francesca; Traverso, Carlo Enrico; Iester, Michele
Abstract : Background . The purpose of this study is to estimate the incidence of choroidal detachment (CD) after XEN gel stent implant surgery and to evaluate the associated factors. Methods . We reviewed the clinical charts of 126 patients who underwent XEN implantation between March 1, 2016, and December 31, 2018 at the University Eye Clinic of Genoa. Ocular, demographics, and perioperative factor were registered and analysed. Univariate and multivariate logistic analysis were performed to investigate factors associated with CD occurrence. Results . Of the 126 patients, 25 (19.8%) developed a choroidal detachment after XEN gel stent implant surgery. The mean period between surgery and CD detection was 5.84 ± 1.77 days. The mean intraocular pressure (IOP) at the time of CD diagnosis was 6.4 ± 3.1 mmHg. Age (OR = 1.10, p < 0.019 ), early postoperative IOP (OR = 0.70, p < 0.001 ), and number of preoperative IOP-lowering drugs (OR = 5.70, p < 0.001 ) were significantly associated with CD presence. Complete resolution was observed in all the cases. Wide-field imaging and ultrasonography were useful tools to diagnose and follow up CD until resolution. Conclusions . When carefully investigated, CD is a relatively common complication after XEN gel stent implant procedure. Older age, lower postoperative IOP, and higher number of preoperative IOP-lowering drugs were significantly associated with the development of CD.